Spearheading environmental change the legacy of Indiana congressman Floyd J. Fithian - May, Jill P.; May, Robert E. 1943- (Purdue University Press, 2022)
"Spearheading Environmental Change: The Legacy of Indiana Congressman Floyd J. Fithian describes the life of a four-term United States congressman, focusing on his role in the emerging environmental movement in late twentieth-century America. Spearheading Environmental Change highlights Fithian's legislative efforts regarding three water-related issues that profoundly concerned Hoosier and midwestern voters: creating a national park on the Indiana shoreline of Lake Michigan; canceling dam construction near Purdue University; and mitigating flooding in the Kankakee River Basin. The book also covers Fithian's positions on ecologically sensitive issues such as pesticides, noise pollution, fossil fuels, and nuclear power. Largely remembered for his participation in the Democratic reform wave that took over Congress in 1975 post-Watergate (the so-called Class of '74) and as an advocate for Hoosier farmers, Fithian has been overlooked for his role as a force to be reckoned with on the House floor when it came to the nation's environmental challenges. Fithian was a highly ethical, pragmatic reformer bent on preserving his country's natural resources. Spearheading Environmental Change gives Fithian the credit he deserves as an environmental warrior on the national stage"--
Keywords: Fithian, Floyd J. -- 1928-2003; Fithian, Floyd James / 1928-2003; Legislators / United States / Biography; Legislators / Indiana / Biography; Environmentalists / United States / Biography; Indiana Dunes National Park (Ind.) / History; Water resources development / Environmental aspects / Indiana / History; Environmentalism / United States / History / 20th century; United States / Politics and government / 1945-1989; Parlementaires / États-Unis / Biographies; Indiana Dunes National Lakeshore (Ind.) / Histoire; Ressources en eau / Exploitation / Aspect de l'environnement / Indiana / Histoire; États-Unis / Politique et gouvernement / 1945-1989; Environmentalism; Environmentalists; Legislators; Politics and government; Water resources development / Environmental aspects; Indiana; Indiana / Indiana Dunes National Park; United States; 1900-1999; Biographies; History; Biografie